Interpersonal Communication of Double Burden Parents Towards Children In Handling Toxic Relationships In The Digital Era In Tanjung Mulia Hilir - Desi Wulandari; Nursapia Harahap (International Journal of Science and Environment (IJSE), 2026)
This study aims to analyze the interpersonal communication of parents with a dual role (double burden) in dealing with toxic relationships with children in the digital era in Tanjung Mulia Hilir. The study used a descriptive qualitative method with a case study approach through interviews and observations. Data analysis was carried out through data reduction, presentation, and drawing conclusions, using triangulation techniques for validity. The results show that effective interpersonal communication, including openness, empathy, and emotional support, plays a crucial role in helping children recognize and exit unhealthy relationships. However, parents' limited time is a barrier to building optimal communication. Furthermore, the development of digital technology also affects the quality of interactions, which tend to be minimal in emotional expression. Therefore, improving digital literacy and interpersonal communication skills is necessary to support healthy relationships between parents and children.